Advances in accounting education teaching and curriculum innovations. Vol. 17 - Rupert, Timothy J.; Kern, Beth Burchfield, 1958- (Bingley, U.K. : Emerald, 2015)
Advances in accounting education : teaching and curriculum innovations publishes both nonempirical and empirical articles dealing with accounting pedagogy. All articles explain how teaching methods or curricula/programs can be improved. Nonempirical papers are academically rigorous, and specifically discuss the institutional context of a course or program, as well as any relevant tradeoffs or policy issues. Empirical reports exhibit sound research design and execution, and develop a thorough motivation and literature review, including references from outside the accounting field, where appropriate.
Second chance homeless shelter : a fraud exercise for introductory and survey courses in accounting / Curtis M. Nicholls, Stacy A. Mastrolia -- The use of alternative quiz formats to enhance students' experiences in the introductory accounting course / Julia M. Camp, Christine E. Earley, Judith M. Morse -- Pedagogy change in undergraduate managerial accounting principles courses : a detailed review of simulation use to support business integration learning, student engagement, teamwork and assessment / James F. Zeigler -- Online accounting degrees : hiring perceptions of accounting professionals / James M. Kohlmeyer III, Larry P. Seese, Terry Sincich -- Statement of cash flows : history, practice, and the classroom / Ann Boyd Davis -- Reconceptualizing instruction on the statement of cash flows : the impact of different teaching methods on intermediate accounting students' learning / Casey McNellis -- Teaching the statement of cash flows and free cash flow estimation when nonarticulation is present / Peter Frischmann, Lela D. "Kitty" Pumphrey, Mukunthan Santhanakrishnan.
Print version record
Keywords: Business & Economics -- Accounting -- General; Accounting; Finance & accounting; Accounting -- Study and teaching; Finance -- Study and teaching